Repair of the middle and posterior compartments of the pelvic floor via perineal and vaginal routes without the use of mesh - technique description and case series - Nogueira,Raquel Ferreira (2020)
ABSTRACT Introduction: Currently, problems such as constipation due to outlet obstruction, rectal/vaginal prolapse and fecal and urinary incontinence have become increasingly more frequent because of the population aging process, with great impact on the quality of life. Objective: To describe a technique for surgical repair of middle/posterior pelvic floor compartments and extra-mucosal rectal wall treatment by transperineal and vaginal approach, using native tissues and present the results in twenty patients submitted to this surgical technique. Method: Patients with symptoms secondary to middle/posterior pelvic floor descent and anatomical changes confirmed by proctological exam and pelvic MRI defecography. Results were evaluated through the Agachan constipation score, using pre- and post-operative questionnaires. Results: Immediate repair of rectocele and musculature, with prompt improvement of constipation, sustained by 42 months. There were no severe complications in the postoperative period. Conclusion: This is an effective technique, with adequate anatomic repair, improvement of constipation scores and with low risk.